AMERICAN AND INDONESIAN VALUES OF WOMAN IDENTITY AND THEIR INFLUENCE ON WOMAN'S PURSUIT OF HAPPINESS AS REFLECTED IN ELIZABETH GILBERT'S EAT PRAY LOVE (2006) AND NH. DINI PADA SEBUAH KAPAL (1973) A COMPARATIVE STUDY - Edi Ardian (Elite : English and Literature Journal, 2014)
AbstractThe differences in cultural backgrounds influence the content of literary works, despite the same theme addressed. The purpose of the research is to compare and contrast an American novel Eat Pray Love (EPL) and Indonesian Pada Sebuah Kapal (PSK) for differences and similarities in the sense of how different cultures influence the heroine in each novel in her pursuit of happiness.  For that purpose, a thematic, descriptive, and comparative analysis is conducted to answer two research problems: 1) what constraint each heroine has to face in her attempts to achieve happiness; and 2) how the novel reflects the different ways in which American and Indonesian values concerning women influence the heroine of each novel. The analysis finds out that the heroine in each novel faces the same marital problem. Both are unhappy in their marriages, but they deal with their problem in different ways. In EPL, the heroine attempts individual redefinition of the self by undergoing material and spiritual search and fulfillment, and finally managed to achieve her true happiness. American individualism allows this. In PSK, the heroine undergoes an internal conflict, attempts for her happiness by committing extramarital relationship but fails to redefine herself and returns to her abusive husband and unhappy marriage. Traditional Javanese norms she strongly believes in do not allow her to strive for her happiness in an ‘unlawful’ way. Different cultures and different eras have their own articulation in literary work. American individualism gives greater priority to individuals, whereas Indonesian communality puts individual after social’s interests.IntisariLatar belakang budaya yang berbeda mempengaruhi dalam perkembangan karya sastra walaupun temanya sama. Tujuan dari penelitian ini adalah untuk membandingkan novel Amerika Eat Pray Love (EPL) dan novel Indonesia Pada Sebuah Kapal (PSK) untuk mencari persamaan dan perbedaan di antara keduanya dengan melihat bagaimana perbedaan budaya tersebut mempengaruhi kedua tokoh wanita di dalam masing-masing novel dalam upaya mereka mencapai kebahagiaan sejati. Analisis tematik dan deskriptif dalam kerangka studi perbandingan sastra digunakan untuk menjawab pertanyaan sebagai berikut: 1) hambatan apa yang dihadapi oleh kedua tokoh wanita tersebut untuk mencapai kebahagiaan; 2) bagaimana kedua novel tersebut menggambarkan perbedaan antara nilai-nilai budaya dan masyarakat Amerika dan Indonesia dalam kaitannya dengan perempuan mempengaruhi perilaku tokoh utama wanita di masing-masing novel tersebut dalam upaya mereka mencari kebahagiaan sejati.  Penelitian menemukan bahwa tokoh wanita pada masing-masing novel menghadapi masalah yang sama dalam perkawinan mereka masing-masing. Kedua tokoh wanita ini tidak bahagia dalam perkawinannya. Pada EPL, tokoh wanita ini berusaha mendefinisikan kembali dirinya melalui sebuah proses pencarian jati diri secara material dan spiritual dan hingga akhirnya kebahagiaan sejati. Individualisme dalam masyarakat Amerika memungkinkan hal ini. Pada PSK, tokoh wanita ini menghadapi konflik bathin, berusaha mencapai kebahagiaan dengan melakukan hubungan di luar nikah tetapi gagal mendefinisikan kembali jati dirinya dan kembali kepada suaminya dan penikahannya tidak bahagia. Norma tradisional budaya Jawa yang dipegangnya dengan teguh tidak membenarkannya mencapai kebahagiaan dengan cara yang ’tidak benar’. Individualism Amerika memberikan prioritas terbesar untuk setiap individu, komunalitas masyarakat dan budaya Indonesia menempatkan kepentingan individual setelah kepentingan sosial.